2015
DOI: 10.1111/joa.12425
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cellular processes in the mesenchyme during palatal development in the absence of Tbx1 reveals complex proliferation changes and perturbed cell packing and polarity

Abstract: The 22q11 deletion syndromes represent a spectrum of overlapping conditions including cardiac defects and craniofacial malformations. Amongst the craniofacial anomalies that are seen, cleft of the secondary palate is a common feature. Haploinsufficiency of TBX1 is believed to be a major contributor toward many of the developmental structural anomalies that occur in these syndromes, and targeted deletion of Tbx1 in the mouse reproduces many of these malformations, including cleft palate. However, the cellular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…A large number of genes and molecular pathways required for palatogenesis have been identified. In addition, recent studies have begun to unravel the extensive crosstalk of various signaling pathways and gene regulatory subnetworks and to integrate molecular mechanisms with cellular processes and cell behavior during palatal shelf growth, patterning, and fusion Kim et al 2015;Lan et al 2015;Brock et al 2016). The abundance of signaling molecules and transcription factors in and the heterogeneity and dynamics of cellular and molecular processes across the developing palatal shelves provide an outstanding paradigm for genetic regulation of mammalian organogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of genes and molecular pathways required for palatogenesis have been identified. In addition, recent studies have begun to unravel the extensive crosstalk of various signaling pathways and gene regulatory subnetworks and to integrate molecular mechanisms with cellular processes and cell behavior during palatal shelf growth, patterning, and fusion Kim et al 2015;Lan et al 2015;Brock et al 2016). The abundance of signaling molecules and transcription factors in and the heterogeneity and dynamics of cellular and molecular processes across the developing palatal shelves provide an outstanding paradigm for genetic regulation of mammalian organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of signaling molecules and transcription factors in and the heterogeneity and dynamics of cellular and molecular processes across the developing palatal shelves provide an outstanding paradigm for genetic regulation of mammalian organogenesis. Whereas creative combination of live imaging techniques with detailed genetic studies has provided unprecedented insight into the cellular mechanisms of palatal fusion (Kim et al 2015), direct measurement of cell behavior during palatal shelf growth and elevation requires new technological advances since palatal explants under current culturing conditions do not fully recapitulate in vivo growth patterns (Brock et al 2016). In addition, major gaps remain in the molecular mechanisms of cleft palate palatogenesis, particularly regarding the roles of and mechanisms involving microRNAs, various environmental factors, and gene-environment interactions (Seelan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Functional experiments targeting different components of the Wnt/PCP signaling highlighted the importance of the ectomesenchyme polarity for the proper facial outgrowth in several developmental time-points. Overall, the rate of cell divisions in Wnt/PCP mutants does not appear to be affected, however, the impaired direction of daughter cell allocation during cell division results in a variety of pathologies, such as shorter and wider facial proportions, abnormal mesenchymal patterning during early palatogenesis or misoriented and misshaped chondrocytes affecting the facial morphometry (Figures 1IIC,D; Le Pabic et al, 2014;Brock et al, 2016;Kaucka et al, 2016). Oriented deposition of daughter cells also represents a core elongation mechanism driving the longitudinal growth of flat facial cartilage composing the mammalian chondrocranium ( Figure 1IIC; Kaucka et al, 2017).…”
Section: Cell and Tissue Dynamics In Early Craniofacial Morphogenesismentioning
confidence: 99%
“…Histological studies have suggested that the anterior PSs “flip up” during elevation while the posterior PSs undergo tissue remodeling and protrusion over the tongue (Walker and Fraser 1956; Jin et al 2010; Yu and Ornitz 2011). Many hypotheses have been proposed for PS elevation, including intrinsic factors, such as regional changes in proliferation (Lan et al 2004; Zhou et al 2013), alterations in mesenchymal cell density (Brock et al 2016), and extracellular matrix remodeling (Morris-Wiman and Brinkley 1993; Mansell et al 2000; Chiquet et al 2016), including hyaluronic acid accumulation (Brinkley and Morris-Wiman 1987; Lan et al 2019). Extrinsic factors such as mandibular growth and depression of the mandible and tongue (Ferguson 1977, 1978; Yu and Yonemitsu 2019) and fetal mouth movements (Friedl et al 2019) have also been invoked.…”
Section: Introductionmentioning
confidence: 99%